Cacophony in Arabic A Research Paper Submitted (مجلة ديالى للبحوث الانسانية, 2022)
Cacophony in ArabicA Research Paper Submitted      This research paper touches upon weird and alien words and expressions interspersed in the verse of some prominent Arab bards. The demonstration takes into account to survey a fairly broad scope within such cacophonous evocable and forms occur. In this regard, the researcher believes it necessary to give an overview of two significant interrelated concepts, i.e. ‘eloquence and rhetoric’. This contradistinction holding between the two terms is given prominence with reference to one of the most important Arabic lexicons. لسان العرب ‘the speech of the Arabs’ by the notable Arab lexicographer Ibn- Mandhour. All in all, the paper has been organized and itemized into:• An overview of eloquence and rhetoric,• Merits and demerits of words and word- formation,• Commentaries are provided wherever necessary,• Banality and Platitude of the usage of certain instanced words and expressions are signalized in the course of this humble study.• Most of the instances cited throughout the research are excerpts from the verse of some prominent Arab bards and scholars.      A conclusion is appended in which the major points are briefly forwarded. This is done as such, yet a lot more remains to be presented, demonstrated and discussed. In fact, this topic is prone to a considerable expansion and more profound exploration.